Inovasi Frugal dan Kepemimpinan yang Berkelanjutan untuk Keunggulan Bersaing: Sebuah Tinjauan Literatur - Devina; Herachwati, Nuri (IPB University, 2024)
This article examines the frugal innovation. Innovation is considered very important so that organization or company can survive. The business industry often faces dynamic change, so the frugal innovation is considered as solution for that. Frugal Innovation uses the limited resource so that consumen can buy with affordable price. The implementation frugal innovation has done in some countries like China and Pakistan. Implementation of frugal innovation at sector of organization or micro small and medium enterprise cannot be separated from the role of leader. Sustainable leadership has influence to the implementation of frugal innovation. It is because sustainable leadership is focus to the purpose and long-term vision of the organization. It will influence to the implementation of frugal innovation. Impelementation of innovation must be consistent and long term. Innovation is a process that aims to create new knowledge and develop workable solutions. This method is used systematic literature review by indentifying twentyone relevant articles taken from the Scopus database which were analyzed. The steps include identifying, screening and eligibility. The results of this research indicate that frugal innovation can be implemented in organizations, companies or micro small and medium enterprises. Impelementing frugal innovation has good impact for organization, company and micro small and medium enterprise. Organization, company and micro small and medium enterprise must survive and adaptive, so that they do and impelement innovation for overcoming the dynamic change. Impelementing innovation can improve the performance of organization or company. This can make organization, company and micro small and medium enterprise can be competitive in the business industry. Frugal innovation is one of the ways to make organizations, companies, and small and medium-sized enterprises gain a competitive advantage in the business industry. This is because frugal innovation can create a more inclusive market because it changes product design, modifies business models, reconfigures the value chain, and satisfies users with limited affordability with a more sustainable approach. The implementation of frugal innovation is also environmentally friendly.